Plant genetic resources for agriculture, plant breeding, and biotechnology: Experiences from Cameroon, Kenya, the Philippines, and Venezuela - Falck-Zepeda, José B.; Zambrano, Patricia; Cohen, Joel I.; Borges, Orangel; Guimarães, Elcio P.; Hautea, Desiree; Kengue, Joseph; Songa, Josephine (International Food Policy Research Institute, 2008)
Local farming communities throughout the world face binding productivity constraints, diverse nutritional needs, environmental concerns, and significant economic and financial pressures. Developing countries address these challenges in different ways, including public and private sector investments in plant breeding and other modern tools for genetic crop improvement. In order to measure the impact of any technology and prioritize investments, we must assess the relevant resources, human capacity, clusters, networks and linkages, as well as the institutions performing technological research and development, and the rate of farmer adoption. However, such measures have not been recently assessed, in part due to the lack of complete standardized information on public plant breeding and biotechnology research in developing countries. To tackle this void, the Food and Agricultural Organization of the United Nations (FAO), in consultation with the International Food Policy Institute (IFPRI) and other organizations, designed a plant breeding and biotechnology capacity survey for implementation by FAO consultants in 100 developing countries. IFPRI, in collaboration with FAO and national experts contracted by FAO to complete in-country surveys, identified and analyzed plant breeding and biotechnology programs in four developing countries: Cameroon, Kenya, the Philippines, and Venezuela. Here, we use an innovation systems framework to examine the investments in human and financial resources and the distribution of resources among the different programs, as well as the capacity and policy development for agricultural research in the four selected countries. Based on our findings, we present recommendations to help sustain and increase the efficiency of publicly- and privately-funded plant breeding programs, while maximizing the use of genetic resources and developing opportunities for GM crop production. Policy makers, private sector breeders, and other stakeholders can use this information to prioritize investments, consider product advancement, and assess the relative magnitude of the potential risks and benefits of their investments.